2018
DOI: 10.3389/fmed.2018.00347
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation Sequencing in Early Diagnosis of Dent Disease 1: Two Case Reports

Abstract: Dent disease 1 is a rare X-linked recessive inherited disease, caused by pathogenic variants in the chloride voltage-gated channel 5 (CLCN5) gene. Dent disease 1 is characterized by low molecular weight (LMW) proteinuria, hypercalciuria, nephrocalcinosis, and chronic kidney disease. Infants may manifest only asymptomatic LMW proteinuria, which increases the difficulty of early diagnosis. We describe two male infants presenting only with nephrotic-range LMW proteinuria observed on examination using urine protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 27 publications
0
7
0
3
Order By: Relevance
“…More than 220 CLCN5 pathogenic mutations have been reported so far. Mutations were found scattered along all exons of the gene and in different protein domains [9,[34][35][36][37][38][39][40][41][42][43][44][45]. Mansour-Hendili et al [9] reported that the majority were missense and frameshift mutations (33.33% and 29.05% respectively) followed by nonsense mutations (17.52%), splicing mutations (12.39%), and large deletions (4.70%).…”
Section: Discussionmentioning
confidence: 99%
“…More than 220 CLCN5 pathogenic mutations have been reported so far. Mutations were found scattered along all exons of the gene and in different protein domains [9,[34][35][36][37][38][39][40][41][42][43][44][45]. Mansour-Hendili et al [9] reported that the majority were missense and frameshift mutations (33.33% and 29.05% respectively) followed by nonsense mutations (17.52%), splicing mutations (12.39%), and large deletions (4.70%).…”
Section: Discussionmentioning
confidence: 99%
“…The proximal tubule represents the site of greatest calcium reabsorption within the renal tubule, and it is mutations in the ClC-5 chloride transporter in this region, encoded by CLCN5, that give rise to Dent disease type 1 [12]. This condition demonstrates an X-linked recessive pattern of inheritance; affected males usually display a triad of low molecular weight (LMW) proteinuria, hypercalciuria and nephrocalcinosis, although the triad may be incomplete at initial presentation [11]. Female carriers are usually asymptomatic, but may occasionally have LMW proteinuria, hypercalciuria or nephrolithiasis [12].…”
Section: Clcn5 Mutationsmentioning
confidence: 99%
“…OCRL mutations, which may result in a spectrum of phenotypes ranging from Dent disease 2 to the more severe Lowe oculocerebrorenal syndrome, account for a further 15% of cases, whilst the underlying genetic mutation remains unascertained in 25% of cases [12]. The varied phenotypes of Dent disease may also include a partial Fanconi syndrome as the initial clue indicating proximal tubular dysfunction [13], whilst nephrolithiasis or haematuria can also feature alongside the cardinal LMW proteinuria [11]. Although genetic conditions with a Fanconi syndrome, including Lowe oculocerebrorenal syndrome (OCRL mutations) and cystinosis (CTNS mutations) may also feature nephrocalcinosis [14,15], it remains more commonly associated with Dent disease 1 (CLCN5 mutations) [16].…”
Section: Clcn5 Mutationsmentioning
confidence: 99%
See 2 more Smart Citations